A systematic review of the effect of prior hypoglycaemia on cognitive function in type 1 diabetes. (February 2020) - Rama Chandran, Suresh; Jacob, Peter; Choudhary, Pratik
Background: The effect of prior hypoglycaemia on cognitive function in type 1 diabetes is an important unresolved clinical question. In this systematic review, we aimed to summarize the studies exploring the impact of prior hypoglycaemia on any aspect of cognitive function in type 1 diabetes. Methods: We used a multidatabase search platform Healthcare Database Advanced Search to search Medline, PubMed, EMBASE, EMCARE, CINAHL, PsycINFO, BNI, HMIC, and AMED from inception until 1 May 2019. We included studies on type 1 diabetes of any age. The outcome measure was any aspect of cognitive function. Results: The 62 studies identified were grouped as severe hypoglycaemia (SH) in childhood (⩽18 years) and adult-onset (>18 years) diabetes, nonsevere hypoglycaemia (NSH) and nocturnal hypoglycaemia (NH). SH in early childhood-onset diabetes, especially seizures and coma, was associated with poorer memory (verbal and visuospatial), as well as verbal intelligence. Among adult-onset diabetes, SH was associated with poorer cognitive performance in the older age (>55 years) group only. Early versus late exposure to SH had a significant association with cognitive dysfunction (CD). NSH and NH did not have any significant association with CD, while impaired awareness of hypoglycaemia was associated with poorer memory and cognitive-processing speeds. Conclusion: The effect of SH on cognitive function is age dependent. Exposure to SH in early childhood (<10 years) and older age groups (>55 years) was associated with a moderate effect on the decrease in cognitive function in type 1 diabetes [PROSPERO ID: CRD42019141321].